The roots of cognitive neuroscience behavioral neurology and neuropsychology - Chatterjee, Anjan; Coslett, H. Branch; Oxford scholarship online (Online service). (New York Oxford University Press, 2014)
This title takes a close look at what we can learn about our minds from how brain damage impairs our cognitive and emotional systems. This approach has a long and rich tradition dating back to the 19th century. With the rise of new technologies, such as functional neuroimaging and non-invasive brain stimulation, interest in mind-brain connections among scientists and the lay public has grown exponentially. Behavioural neurology and neuropsychology offer critical insights into the neuronal implementation of large-scale cognitive and affective systems.
Includes bibliographical references and index.
Keywords: Cognitive neuroscience; Clinical neuropsychology; Neuropsychiatry; Electronic books